Identification of linear polyubiquitin chain immunoreactivity in tau pathology of Alzheimer's disease. (11th June 2019) - Nakayama, Yoshiaki; Sakamoto, Shinji; Tsuji, Kazumi; Ayaki, Takashi; Tokunaga, Fuminori; Ito, Hidefumi
Highlights: Our antibody recognizes linear polyubiquitin chain (L-Ub). We examined the hippocampus of patients with Alzheimer's disease. A subset of abnormally accumulated tau proteins was L-Ub immunopositive. L-Ub is added to a subset of lys48-linked polyubiquitinated tau aggregation. Abstract: Characteristic neuropathological structures observed in Alzheimer's disease, such as neurofibrillary tangles and dystrophic neurites of senile plaques, are universally ubiquitinated. Eight linkage types of polyubiquitin chains are known, and each type of chain exerts different intracellular action. Among them, linear polyubiquitin chain was recently reported to be associated with the pathomechanism of neuronal cell death. We therefore generated a novel antibody that specifically recognizes linear polyubiquitin chain. We immunohistochemically examined the brains of patients with Alzheimer's disease. A subset of neurofibrillary tangles, dystrophic neurites of senile plaques, and neuropil threads were evident to be immunopositive for linear polyubiquitin chains, but their number was fewer than those recognized by the antibody against K48-linked polyubiquitin chains. Double immunofluorescence investigation showed that in certain neurofibrillary tangles, a part of K48-linked polyubiquitin-immunopositive structures were immunolabeled for linear polyubiquitin chains. Our results imply that linear polyubiquitination follows K48-linked polyubiquitination in abnormally accumulated tau proteins in Alzheimer's disease, and imply involvement in its neurodegeneration.